Safety of Sea Transportation proceedings of the 12th International Conference on Marine Navigation and Safety of Sea Transportation (TransNav 2017), June 21-23, 2017, Gdynia, Poland - Weintrit, Adam; Neumann, Tomasz (CRC Press/Balkema, 2020)
The 12th International Conference on Marine Navigation and Safety of Sea Transportation (TransNav 2017) will take place on June 21-23 in Gdynia, Poland. Main themes of this conference include: electronic navigation, route planning, mathematical models, methods and algorithms, ships manoeuvring, navigational risks, Global Navigation Satellite Systems (GNSS), Automatic Identification System (AIS), marine radar, anti-collision, dynamic positioning, visualization of data, hydrometereological aspects and weather routing, safety at sea, inland navigation, autonomous water transport, communications and global maritime distress and safety system (GMDSS), port ant routes optimum location and magnetic compasses.